PENGARUH PENGUNGKAPAN IDENTITAS ETIS ISLAM, AGENCY COST DAN MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN (STUDI PADA BANK UMUM SYARIAH PERIODE 2010-2014) - Muhibban, Azhara; Basri, Hasan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study aimed to examine the influence of the Islamic ethical identity disclosure, agency cost, and intellectual capital to the financial performance proxied by Return on equity (ROE) in Islamic commercial banks in 2010-2014.secondary data were used from annual reports were published on the website each Islamic banks between 2010-2014. This study is a hypothesis testing research, by using purposive sampling method, so there are seven Islamic banks are the object of research. The analytical method used is multiple linear regression analysis. The results of this study shows that simultaneous of the Islamic ethical identity disclosure, agency cost and intellectual capital have effect on the financial performance proxy by ROE on an Islamic commercial bank in 2010-2014. Partially only the Islamic ethical identity disclosure have positive effect but not significant on the financial performance of Islamic banks, while the agency cost and intellectual capital have positive and significant effect on the financial performance proxied by the ROE on an Islamic commercial bank in 2010-2014..Keywords: Islamic ethical identity disclosure, agency cost, intellectual capital and financialperformance.